An intervention programme for weight management in overweight and obese Malaysian adults - Tan, Pui Yee (2020)
The prevalence of obesity and its co-morbidities in the Malaysian population has been increasing dramatically through the past decade, and has now become the leading preventable cause of morbidity and mortality in the Malaysian population. The main aim of this doctoral thesis was to develop a dietary intervention programme tailored according to an individual’s food preference, cultural habit and genetic makeup (namely fat mass and obesity-associated gene (FTO) and beta 2-adrenergic receptor (ADRB2) gene). Further, this project aimed to manage body weight and reduce metabolic risk factors through, the modelled dietary intervention in overweight and obese Malaysian adults (Malaysian Malays, Chinese and Indians) (Chapter 6). Thereafter, this project investigated the individual and combined response of the gene variants (FTO and ADRB2 genes) on the post-intervention (6-month period) differences in anthropometric and cardio-metabolic parameters (Chapters 7 & 8).